Emergence of Xin demarcates a key innovation in heart evolution. - Shaun E Grosskurth; Debashish Bhattacharya; Qinchuan Wang; Jim Jung-Ching Lin (PLoS ONE)
The mouse Xin repeat-containing proteins (mXinalpha and mXinbeta) localize to the intercalated disc in the heart. mXinalpha is able to bundle actin filaments and to interact with beta-catenin, suggesting a role in linking the actin cytoskeleton to N-cadherin/beta-catenin adhesion. mXinalpha-null mouse hearts display progressively ultrastructural alterations at the intercalated discs, and develop cardiac hypertrophy and cardiomyopathy with conduction defects. The up-regulation of mXinbeta in mXinalpha-deficient mice suggests a partial compensation for the loss of mXinalpha. To elucidate the evolutionary relationship between these proteins and to identify the origin of Xin, a phylogenetic analysis was done with 40 vertebrate Xins. Our results show that the ancestral Xin originated prior to the emergence of lamprey and subsequently underwent gene duplication early in the vertebrate lineage. A subsequent teleost-specific genome duplication resulted in most teleosts encoding at least three genes. All Xins contain a highly conserved beta-catenin-binding domain within the Xin repeat region. Similar to mouse Xins, chicken, frog and zebrafish Xins also co-localized with beta-catenin to structures that appear to be the intercalated disc. A putative DNA-binding domain in the N-terminus of all Xins is strongly conserved, whereas the previously characterized Mena/VASP-binding domain is a derived trait found only in Xinalphas from placental mammals. In the C-terminus, Xinalphas and Xinbetas are more divergent relative to each other but each isoform from mammals shows a high degree of within-isoform sequence identity. This suggests different but conserved functions for mammalian Xinalpha and Xinbeta. Interestingly, the origin of Xin ca. 550 million years ago coincides with the genesis of heart chambers with complete endothelial and myocardial layers. We postulate that the emergence of the Xin paralogs and their functional differentiation may have played a key role in the evolutionary development of the heart.